Bupivacaine Injection in the Extra Ocular Muscle of Rabbits: Analysis of Global and Orbital Layers. (2nd August 2020) - Hopker, Luisa Moreira; de Moraes, Marco Aurélio Senff; Nitsch, Rodrigo; Pasqual, Gabriela Wahab; Cavagnari, Pamela; Kusma, Solena Ziemer; Moreira, Luciane; Zanoteli, Edmar; Allemann, Norma
ABSTRACT: Purpose: To verify the cross sectional area (CSA) of fibers positive for myosin type 1 in the global and orbital layers after bupivacaine (BUP) injection in the superior rectus of the right eye of rabbits. Materials and Methods: A total of 40 rabbits were studied; 32 specimens received a 0.3 mL injection of BUP at 1.5% in the superior rectus of the right eye and were euthanised after 7, 28, 60 and 92 days. Another eight rabbits were used as the control group. Immunohistochemical analysis was performed using anti-slow myosin (type 1) antibodies. The ImageJ software was used to measure the CSA of the fibers. Six slides were excluded from the analysis. Finally, 7, 204 fibers were counted and statistically analysed. Results: The mean CSA was 0.040 µm 2 for all the studied fibers. For the orbital layer, mean CSA was 0.038 µm 2, whereas the global area measured 0.042 µm 2 . No statistically significant differences were observed when comparing the orbital layer groups. However, when comparing the mean CSA in the global layer of the control group with the 60-day group an increase was found (0.0339 ± 0.0062 versus 0.0503 ± 0.0114; p = .009). Conclusion: This study revealed that 60 days after BUP injection, the extra ocular muscle of rabbits presented an increase in the CSA of myosin 1 type fibers in the global layer.